Psicología cognoscitiva y esquemas conceptuales de los alumnos - Driver, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
There are three main sections in this paper. The first section presents an overview of the research that has been undertaken into students' conceptions relating to mechanics. One central feature of students' «intuitive mechanics» is the association between their notions of force and motion. The consequences of such ideas for students' reasoning about various static and dynamic systems are described. A number of general features of students' alternative conceptions are then outlined. The second section outlines current perspectives on learning with particular emphasis being paid to the constructivist perspective; a perspective which emphasises the active role of lear-ners in the construction of their knowledge. The pedagogical consequences of adopting this perspective are outlined in the third section.